HDL-C levels added to the MELD score improves 30-day mortality prediction in Asian patients with cirrhosis. Issue 7 (July 2022) - Wang, Yue; Shen, Wenjuan; Huang, Fang; Yu, Chenyan; Xi, Liting; Gao, Jingwen; Yin, Minyue; Liu, Xiaolin; Lin, Jiaxi; Liu, Lu; Zhang, Huixian; Zhu, Jinzhou; et al.
Objectives: Lower high-density lipoprotein cholesterol (HDL-C) levels have been observed in chronic liver disease patients. The aim of this study was to develop a model that incorporates HDL-C levels and the Model for End-stage Liver Disease (MELD) score to predict 30-day mortality in Asian cirrhosis patients. Methods: Cirrhosis patients were recruited from two hospitals in this retrospective observational study. Propensity score matching was used. The model's performance was evaluated, including its ability to predict 30-day mortality, accuracy, and clinical utility. Net reclassification improvement (NRI) and integrated discrimination improvement (IDI) were calculated. Results: The HDL-C + MELD model showed good ability to predict 30-day mortality (area under the curve, 0.784; sensitivity, 0.797; specificity, 0.632), which was better than that of the MELD score alone. It also showed good calibration and a net benefit for all patients, which was better than that of the MELD score, except at the threshold probability. NRI and IDI results confirmed that adding HDL-C levels to the MELD score improved the model's performance in predicting 30-day mortality. Conclusion: We added HDL-C levels to the MELD score to predict 30-day mortality in Asian patients with cirrhosis. The HDLC + MELD model shows good ability to predict 30-day mortality and clinical utility.